New Phraseological Compounds with “Dywan” in Modern Polish Language - Ignatowicz-Skowrońska, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The subject of discussion in this article are new phraseological compounds with the component dywan, which have been in use since the 1990s in Polish texts. These compounds, not yet recorded in language dictionaries, have emerged under the influence of the English language. They refer to phrases related to the English combinations of roll out the red carpet (for someone) and pull from under someone // something or pull the rug from under someone’s feet. The article analyses the ways these expressions function in Polish texts, considering their formal structure, compatibility with minimal context, and meaning. The research shows that these new combinations, inspired by the English language, consist of three phrases: ktoś rozwinął, rozwija, rozłożył, rozkłada less commonly rozściela, rozścieli, rozpostarł, rozpościerał czerwony dywan, less commonly czerwone dywany dla kogoś, przed kimś – meaning ‘someone officially and attentively invites or receives important guests, usually from the worlds of politics, business, culture, etc.’; ktoś less commonly coś rozwinął(o), rozwija, rozłożył(o), rozkłada, less commonly rozściela, rozścieli(o), rozpostarł(o), rozpościerał(o) czerwony dywan, less commonly czerwone dywany dla kogoś, czegoś, przed kimś, przed czymś – meaning ‘someone, less commonly something, opens up to someone, something, invites someone, something to something, somewhere; someone, something facilitates something for someone, the acquisition of something, getting somewhere, especially through special treatment’; ktoś less commonly coś wyciąga, wyciągnął (-ęło), wyrywa, wyrwał(o) etc. dywan, dywanik, chodnik spod (nóg, stóp) komuś, kogoś, czego – meaning ‘someone, less commonly something, surprises, has surprised someone with something, disorients, has disoriented someone; weakens, has weakened someone, something, withdraws, has withdrawn support for someone, something, harms, has harmed someone, something’.